Determinants of Salesperson Performance: Motivation, Training, Job Satisfaction, and Compensation at PT. ABC Dealers in Bogor and Depok - Sudrajat Jonathans; Ardi Kho; Richard Andre Sunarjo; Sylvia Samuel (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Employee performance is a key determinant of sales improvement and is significant in the automobile industry, as marketing/sales personnel directly interact with customers during the sales process. From 2020 to 2024, PT. ABC dealerships in Bogor had an achievement rate of only 49.2% to 92.8%, and Depok 50.5% to 85.6%, thus showing a performance gap and untapped potential in Bogor and Depok. Objective: This study aimed to analyze the effect of work motivation, job training, job satisfaction, and compensation on the performance of sales employees (salespersons) at PT. ABC automobile dealerships in the Bogor and Depok area. Methods: The research respondents were 288 sales employees from a total of 306 sales employees of PT. ABC outlets in the Bogor and Depok area. The study employed a quantitative research approach, with SEM-based analysis using AMOS as the data analysis technique. Results: The results show that career development, compensation, and job satisfaction respectively have a positive and significant effect on employee performance. Though, work motivation and job training do not affect employee performance. The model results suggested that career development (β=0.138, p=0.003), compensation (β=0.254, p=0.001), and job satisfaction (β=0.181, p=0.014) were significant predictors of work performance. Conclusion: Training has no impact on job satisfaction and performance, whereas career development and compensation enhance the job satisfaction and performance of employees. Motivation boosts satisfaction but does not lead to improved performance. These relationships are partially mediated by job satisfaction. PT. ABC needs to improve career paths, compensation transparency, and recognition systems.